A deliberative approach to post legislative scrutiny? Lessons from Australia's ad hoc approach. Issue 3 (2nd July 2020) - Moulds, Sarah
ABSTRACT: The elusive concept of post legislative scrutiny (PLS) is slowly starting to capture the attention of Westminster inspired Parliaments around the world with its promise of improving the implementation and quality of law making through systematic review, with benefits of the citizen on the ground. Assumptions are made within the idea of PLS about who should be responsible for the scrutiny (the Parliament) and how it should occur in practice (often led and supported by Executive agencies). However, in many jurisdictions, including Australia, the term 'PLS' is not well known because the act of post-legislative scrutiny occurs on an ad hoc basis, without any clear systematic or prescribed framework for monitoring how, when or why it might occur. This gives rise to concerns that the quality of PLS occurring in jurisdictions like Australia might be lacking and demands for a more structured approach. This article shares these concerns but argues that the experience of PLS in Australia offers important insights how to invest PLS systems with the type of deliberative features that are necessary to ensure that scrutiny of implementation and lawmaking delivers meaningful outcomes for citizens on the ground.